PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Irfan Saepullah; Paniran; Susana Dewi (Universitas La Tansa Mashiro, 2023)
Going concern audit opinion is the level of viability of a company which means that the company is considered able to survive in its business activities in the long term and will not be liquidated in the short term. This study aims to examine the Effect of Liquidity (Quick Ratio), Company Size and Profitability (Return On Assets) on Going Concern Audit Opinions in Manufacturing Companies in the Consumer Goods Industry Sector for the 2017-2021 Period. This research method uses quantitative methods, the samples used in this study are all consumer goods industrial sector companies listed on the IDX The results of this study indicate that liquidity (Quick Ratio) has a significant effect on Going Concern Audit Opinion, company size has no effect on Going Concern Audit Opinion and Profitability (return on assets) has no significant effect on Going Concern Audit Opinion. The termination coefficient shows a value of 21.7% which means that the Going Concern Audit Opinion can be influenced by the variables of Liquidity (QR), Company Size (LN = Total Assets) and Profitability (ROA). And the remaining 78.3% is influenced by other variables.